Application of a Bi / BiOCl composite nanophotocatalyst in photocatalytic degradation of volatile organic compounds
Through the surface plasmon resonance effect and solvothermal preparation technology of Bi/BiOCl composite nanophotocatalyst, the complex synthesis and high cost of existing photocatalytic materials are solved, and the efficient degradation of volatile organic compounds under visible light is achieved, which is suitable for industrial applications. .
Patent Information
- Application Number
- CN202210754517.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-29
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2042-06-29
AI Technical Summary
The synthesis process of existing photocatalytic materials is complex, has high cost, has high energy consumption and low catalytic activity, making it difficult to effectively degrade volatile organic matter.
Bi/BiOCl composite nanophotocatalyst is used to enhance the absorption of visible light by surface plasmon resonance effect, and Bi/BiOCl composite nanophotocatalyst is prepared in combination with solvothermal method to improve its catalytic performance under visible light, and catalytic is improved through dark adsorption process efficiency.
It realizes efficient degradation of volatile organic compounds under visible light, simplifies the material preparation process, reduces costs, and improves catalytic activity, making it suitable for industrial applications.
Smart Images

Figure HDA0003720369700000011 
Figure HDA0003720369700000012 
Figure HDA0003720369700000021
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photocatalysis, and specifically relates to application of a Bi / BiOCl composite nano-photocatalyst in photocatalytic degradation of volatile organic matter. Background Art
[0002] In recent years, the hazards of unorganized exhaust gas emitted from workshops have become increasingly prominent, especially in the light textile industry, machinery, and electronic information manufacturing workshops, where the emission of unorganized exhaust gas threatens the health of workers. However, since the main component of unorganized exhaust gas is volatile organic compounds (VOCs), it belongs to non-point source emissions and may exist in any link of the process production, so it is currently difficult to effectively control it from the source. Therefore, it is particularly important to seek an efficient, feasible and convenient way to deal with unorganized exhaust gas emissions in workshops.
[0003] Photocatalysis is considered to be one of the most promising technologies. It can effectively use ultraviolet light and even visible light to completely decompose organic pollutants into inorganic small molecules such as water and carbon dioxide without generating secondary pollution. At present, semiconductor materials are one of the most widely used photocatalytic materials because of their high activity, low cost and high stability. Among them, bismuth oxychloride (BiOCl), as a new type of photocatalyst, has low toxicity and excellent photocatalytic performance. However, the band gap of BiOCl is about 3.4eV. In theory, it can only absorb ultraviolet light, and electron-hole pairs are prone to recombination during the photocatalytic reaction, which greatly limits its application. Therefore, many studies are also committed to expanding the light absorption range, promoting the separation of photogenerated charges, reducing the recombination rate of electron-hole pairs, and improving product selectivity through element doping, construction of composite materials, lattice regulation and other technologies. These methods have played a role in improving the catalytic efficiency of photocatalysts to a certain extent, but there are defects such as complex material synthesis process, high cost, and difficulty in meeting the needs of practical applications. Summary of the invention
[0004] In view of the defects of the above-mentioned prior art in the photocatalytic material synthesis process being complex, high cost, high energy consumption and low catalytic activity, the present invention provides an application of a Bi / BiOCl composite nano-photocatalyst in the photocatalytic degradation of volatile organic compounds.
[0005] In order to achieve the above-mentioned purpose, the following technical solutions are included:
[0006] The invention discloses an application of a Bi / BiOCl composite nano-photocatalyst in the photocatalytic degradation of volatile organic compounds.
[0007] As a preferred embodiment of the present invention, the following photocatalytic degradation method is included: placing the Bi / BiOCl composite nano-photocatalyst in a medium containing volatile organic matter, and catalytically degrading the volatile organic matter under visible light.
[0008] As a preferred embodiment of the present invention, the volatile organic compound includes at least one of toluene and formaldehyde.
[0009] Bi can enhance the absorption of visible light by Bi-based materials through the surface plasmon resonance effect (SPR), thereby improving the photocatalytic performance under visible light. Therefore, the inventors of the present invention prepared a Bi / BiOCl composite nano-photocatalyst, in which the Bi in the catalyst improves the photocatalytic performance of BiOCl through the SPR effect, so as to achieve the purpose of catalytic degradation of organic pollutants under visible light.
[0010] As a preferred embodiment of the present invention, the catalyst is placed in a medium containing volatile organic substances and then undergoes a dark adsorption process.
[0011] The dark adsorption time is 1 to 3 hours.
[0012] Before visible light is introduced for photocatalytic degradation, the catalyst is darkly adsorbed. At this time, the catalyst adsorbs volatile organic matter in the catalyst. The concentration of organic matter adsorbed by the catalyst is relatively high. When visible light irradiates the catalyst, the organic matter adsorbed on the catalyst begins to degrade, which can accelerate the degradation rate.
[0013] The catalytic degradation method is a static reaction, which is simple to operate and can degrade volatile organic compounds without further dispersing the catalyst. This indirectly reflects that the photocatalyst of the present invention has a strong ability to adsorb volatile organic compounds and catalytic activity.
[0014] As a preferred embodiment of the present invention, the mass ratio of the Bi / BiOCl composite nano-photocatalyst to the volatile organic matter is 1:(0.1-2).
[0015] As a preferred embodiment of the present invention, the mass ratio of the Bi / BiOCl composite nano-photocatalyst to volatile organic matter is 1:0.675.
[0016] As a preferred embodiment of the present invention, the preparation method of the Bi / BiOCl composite nano-photocatalyst comprises the following steps: dissolving a bismuth salt in an organic solvent, then adding a chloride salt to form a mixed solution, and heating the mixed solution to react to obtain a Bi / BiOCl composite nano-photocatalyst.
[0017] The method for preparing the Bi / BiOCl composite nano-photocatalyst of the present invention is a solvothermal method, which has the advantages of simple operation, high yield, uniform microscopic size of the product and controllable morphology.
[0018] As a preferred embodiment of the present invention, the reaction temperature is 180-240°C.
[0019] As a preferred embodiment of the present invention, the reaction temperature is 220°C.
[0020] Since the present invention needs to prepare a nanocatalyst composited with Bi and BiOCl, whether it can form Bi simple substance and BiOCl is related to the control of the conditions in the preparation process. The inventors of the present invention have found through a large number of experiments that when the reaction temperature is equal to or less than 160°C, Bi simple substance does not appear in the reaction product, and the product is only BiOCl. It can be seen that the reaction temperature obviously affects the generation of Bi simple substance. Further, the inventors of the present invention found that when the reaction temperature is within the range of 180 to 240°C, not only is Bi simple substance obviously present in the product, but also the microscopic morphology of the formed Bi / BiOCl composite nanophotocatalyst is a spherical shape with a relatively uniform size, and the size of the particles is at the nanometer scale. The specific surface area of the catalyst is relatively large, which is more conducive to the adsorption of volatile organic compounds.
[0021] As a preferred embodiment of the present invention, the reaction time is 6 to 24 hours.
[0022] As a further preferred embodiment of the present invention, the reaction time is 12 to 24 hours.
[0023] The inventors of the present invention found that in the method of the present invention, the target product can be obtained after 6 hours of reaction. The preferred reaction time of the present invention is 12 to 24 hours. At this time, the Bi / BiOCl composite nano-photocatalyst product obtained by the reaction has uniform microscopic size and relatively good dispersion effect of Bi element, which provides a basis for the next step of photocatalytic degradation of volatile organic compounds.
[0024] As a preferred embodiment of the present invention, the organic solvent includes ethylene glycol; the bismuth salt includes at least one of bismuth nitrate pentahydrate and bismuth chloride; and the chloride salt includes at least one of potassium chloride and sodium chloride.
[0025] When the organic solvent is ethylene glycol, in the process of preparing Bi / BiOCl composite nano-photocatalyst, ethylene glycol acts as a solvent, template agent, and reducing agent. 3+ When used as a template, ethylene glycol plays a role in regulating the morphology of the product BiOCl, resulting in the formation of nano-spherical Bi / BiOCl composite nano-photocatalysts, further increasing the specific surface area of the catalyst. In addition, ethylene glycol itself is a reducing agent, and the higher the reaction temperature, the stronger its reducing ability. As the reaction synthesis temperature increases, Bi 3+The amount of Bi reduced to single substance increases continuously, and because Bi single substance has surface plasmon resonance effect, it can activate and / or improve the visible light activity of Bi / BiOCl. Therefore, within a certain temperature range, as the reaction temperature increases, the amount of Bi single substance increases continuously, and the photocatalytic activity increases.
[0026] As a preferred embodiment of the present invention, the concentration of the bismuth salt in the mixed solution is 0.01-0.1 mol / L; the molar ratio of the bismuth salt to the chloride salt is 1:(1-2).
[0027] As a further preferred embodiment of the present invention, the concentration of the bismuth salt in the mixed solution is 0.05 mol / L; the molar ratio of the bismuth salt to the chloride salt is 1:1.
[0028] As a preferred embodiment of the present invention, the forming of the mixed solution further comprises: stirring for 30-60 minutes.
[0029] As a preferred embodiment of the present invention, when the Bi / BiOCl composite nano-photocatalyst is obtained by the above method, it is further subjected to washing and drying steps to remove impurities in the product.
[0030] As a preferred embodiment of the present invention, the detergent used for washing is at least one of ethanol and deionized water.
[0031] As a preferred embodiment of the present invention, the drying conditions are: temperature is 60° C., and time is 6-12 hours.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] (1) The present invention applies Bi / BiOCl composite nano-photocatalyst to the photocatalytic degradation of volatile organic compounds, wherein the Bi element in the catalyst enhances the absorption capacity of BiOCl to visible light through the SPR effect, so that BiOCl absorbs only in the ultraviolet light band and can absorb in the visible light band. The photocatalytic activity of Bi / BiOCl composite nano-photocatalyst in the visible light band is utilized to degrade volatile organic compounds, providing a new path for efficiently and conveniently solving the problem of unorganized organic waste gas pollution in workshops.
[0034] (2) There are also a large number of surface oxygen vacancies on the Bi / BiOCl composite nano-photocatalyst of the present invention, and the oxygen vacancies can also significantly promote the separation of photogenerated electron-hole pairs and improve the photocatalytic activity of the catalyst.
[0035] (3) The Bi / BiOCl composite nano-photocatalyst prepared by the present invention has uniform microscopic size and large specific surface area, and can effectively adsorb volatile organic compounds and increase the efficiency of photocatalytic degradation of volatile organic compounds.
[0036] (4) The method for preparing the photocatalyst and photocatalytically degrading volatile organic compounds of the present invention is simple and easy to operate, and can be applied in large-scale industrial applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 It is the XRD spectra of the products prepared in Examples 1 to 4 and Comparative Example 1, wherein Bi / BiOCl-180, Bi / BiOCl-200, Bi / BiOCl-220, Bi / BiOCl-240 and BiOCl correspond to the products prepared in Examples 1 to 4 and Comparative Example 1, respectively.
[0038] Figure 2 SEM images of the products obtained in Example 3(a) and Comparative Example 1(b).
[0039] Figure 3 The UV-visible diffuse reflectance spectra of the products obtained in Example 3 (Bi / BiOCl-220) and Comparative Example 1 (BiOCl) are shown. DETAILED DESCRIPTION
[0040] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below through specific embodiments.
[0041] Example 1
[0042] Weigh 4 mmol of bismuth nitrate pentahydrate into a beaker, add 80 mL of ethylene glycol, and stir thoroughly at room temperature for 20 min; then add 4 mmol of sodium chloride and stir thoroughly at room temperature for 30 min; transfer the resulting mixed solution to a 100 mL polytetrafluoroethylene reactor for solvothermal reaction at 180°C for 12 h; after the reaction is completed, cool to room temperature and filter with suction, the filter membrane is a 0.22 μm organic microporous filter membrane; after filtration, wash with ethanol and deionized water three times respectively, and after drying the sample at 60°C for 12 h, a composite nano-photocatalyst is obtained, which is recorded as Bi / BiOCl-180.
[0043] Photocatalytic activity test process: At room temperature, 0.40g of the Bi / BiOCl-180 composite nano-photocatalyst of this embodiment is placed in a 30cm*30cm*30cm closed reactor, which contains 10ppm of volatile organic matter toluene. The catalyst darkly adsorbs toluene gas in the reactor for 1h, and then turns on an 8W LED fluorescent line light (white light) to irradiate the catalyst material. The change in the concentration of toluene in the reactor can be detected by a gas chromatograph. The content and degradation rate of toluene are calculated by the peak area of toluene in the chromatographic peak.
[0044] The photocatalytic activity of the prepared Bi / BiOCl-180 composite nano-photocatalyst was measured by degrading toluene under visible light. In this embodiment, the degradation rate of the Bi / BiOCl-180 composite nano-photocatalyst for catalytic degradation of toluene reached 25.6% within 30 minutes.
[0045] Example 2
[0046] Weigh 4 mmol of bismuth nitrate pentahydrate into a beaker, add 80 mL of ethylene glycol, and stir thoroughly at room temperature for 20 min; then add 4 mmol of sodium chloride and stir thoroughly at room temperature for 30 min; transfer the resulting mixed solution to a 100 mL polytetrafluoroethylene reactor for solvothermal reaction at 200 °C for 12 h; after the reaction is completed, cool to room temperature and filter with a 0.22 μm organic microporous filter membrane; after filtration, wash with ethanol and deionized water three times respectively, and dry the sample at 60 °C for 12 h to obtain a composite nano-photocatalyst, recorded as Bi / BiOCl-200.
[0047] Photocatalytic activity test process: At room temperature, 0.40g of the Bi / BiOCl-200 composite nano-photocatalyst of this embodiment is placed in a 30cm*30cm*30cm closed reactor, which contains 10ppm of volatile organic matter toluene. The catalyst darkly adsorbs toluene gas in the reactor for 1h, and then turns on an 8W LED fluorescent line light (white light) to irradiate the catalyst material. The change in the concentration of toluene in the reactor can be detected by a gas chromatograph. The content and degradation rate of toluene are calculated by the peak area of toluene in the chromatographic peak.
[0048] The photocatalytic activity of the prepared Bi / BiOCl-200 composite nano-photocatalyst was measured by degrading toluene under visible light. In this embodiment, the degradation rate of the Bi / BiOCl-200 composite nano-photocatalyst for catalytic degradation of toluene reached 42.1% within 30 minutes.
[0049] Example 3
[0050] Weigh 4 mmol of bismuth nitrate pentahydrate into a beaker, add 80 mL of ethylene glycol, and stir thoroughly at room temperature for 20 min; then add 4 mmol of sodium chloride and stir thoroughly at room temperature for 30 min; transfer the resulting mixed solution to a 100 mL polytetrafluoroethylene reactor for solvothermal reaction at 220°C for 12 h; after the reaction is completed, cool to room temperature and filter with suction, the filter membrane is a 0.22 μm organic microporous filter membrane; after filtration, wash with ethanol and deionized water three times respectively, and after drying the sample at 60°C for 12 h, a composite nano-photocatalyst is obtained, which is recorded as Bi / BiOCl-220.
[0051] Photocatalytic activity test process: At room temperature, 0.40g of the Bi / BiOCl-220 composite nano-photocatalyst of this embodiment is placed in a 30cm*30cm*30cm closed reactor, which contains 10ppm of volatile organic matter toluene. The catalyst darkly adsorbs toluene gas in the reactor for 1h, and then turns on an 8W LED fluorescent line light (white light) to irradiate the catalyst material. The change in the concentration of toluene in the reactor can be detected by a gas chromatograph. The content and degradation rate of toluene are calculated by the peak area of toluene in the chromatographic peak.
[0052] The photocatalytic activity of the prepared Bi / BiOCl-220 composite nano-photocatalyst was measured by degrading toluene under visible light. In this embodiment, the degradation rate of the Bi / BiOCl-220 composite nano-photocatalyst for catalytic degradation of toluene reached 54.9% within 30 minutes.
[0053] Cycle experiment: The Bi / BiOCl-220 composite nano-photocatalysts after the photocatalytic activity test were collected and the collected materials were cycled through the above photocatalytic activity test process. The results showed that the catalytic activities from the first to the fourth cycle were 54.9%, 52.1%, 53.7% and 50.4%, respectively. It can be seen that after four cycles, the degradation rate of the catalyst for toluene is still maintained above 50%, indicating that the Bi / BiOCl composite nano-photocatalyst still maintains a stable photocatalytic activity.
[0054] Example 4
[0055] Weigh 4 mmol of bismuth nitrate pentahydrate into a beaker, add 80 mL of ethylene glycol, and stir thoroughly at room temperature for 20 min; then add 4 mmol of sodium chloride and stir thoroughly at room temperature for 30 min; transfer the resulting mixed solution to a 100 mL polytetrafluoroethylene reactor for solvothermal reaction at 240°C for 12 h; after the reaction is completed, cool to room temperature and filter with suction, the filter membrane is a 0.22 μm organic microporous filter membrane; after filtration, wash with ethanol and deionized water three times respectively, and after drying the sample at 60°C for 12 h, a composite nano-photocatalyst is obtained, which is recorded as Bi / BiOCl-240.
[0056] Photocatalytic activity test process: At room temperature, 0.40g of the Bi / BiOCl-240 composite nano-photocatalyst of this embodiment is placed in a 30cm*30cm*30cm closed reactor, which contains 10ppm of volatile organic matter toluene. The catalyst darkly adsorbs toluene gas in the reactor for 1h, and then turns on an 8W LED fluorescent line light (white light) to irradiate the catalyst material. The change in the concentration of toluene in the reactor can be detected by a gas chromatograph. The content and degradation rate of toluene are calculated by the peak area of toluene in the chromatographic peak.
[0057] The photocatalytic activity of the prepared Bi / BiOCl-240 composite nano-photocatalyst was measured by degrading toluene under visible light. In this embodiment, the degradation rate of the Bi / BiOCl-240 composite nano-photocatalyst for catalytic degradation of toluene reached 47.5% within 30 minutes.
[0058] Example 5
[0059] Weigh 4 mmol of bismuth nitrate pentahydrate into a beaker, add 80 mL of ethylene glycol, and stir thoroughly at room temperature for 20 min; then add 6 mmol of sodium chloride and stir thoroughly at room temperature for 30 min; transfer the resulting mixed solution to a 100 mL polytetrafluoroethylene reactor for solvothermal reaction at a reaction temperature of 220°C for 6 h; after the reaction is completed, cool to room temperature and filter with a 0.22 μm organic microporous filter membrane; after filtration, wash with ethanol and deionized water three times respectively, and dry the sample at 60°C for 12 h to obtain a composite nano-photocatalyst.
[0060] Example 6
[0061] Weigh 4 mmol of bismuth nitrate pentahydrate into a beaker, add 80 mL of ethylene glycol, and stir thoroughly at room temperature for 20 min; then add 4 mmol of sodium chloride and stir thoroughly at room temperature for 30 min; transfer the resulting mixed solution to a 100 mL polytetrafluoroethylene reactor for solvent thermal reaction at a reaction temperature of 220°C for 18 h; after the reaction is completed, cool to room temperature and filter with a 0.22 μm organic microporous filter membrane; after filtration, wash with ethanol and deionized water three times respectively, and dry the sample at 60°C for 12 h to obtain a composite nano-photocatalyst.
[0062] Example 7
[0063] Weigh 4 mmol of bismuth nitrate pentahydrate into a beaker, add 80 mL of ethylene glycol, and stir thoroughly at room temperature for 20 min; then add 4 mmol of sodium chloride and stir thoroughly at room temperature for 30 min; transfer the resulting mixed solution to a 100 mL polytetrafluoroethylene reactor for solvothermal reaction at 220°C for 24 h; after the reaction is completed, cool to room temperature and filter with a 0.22 μm organic microporous filter membrane; after filtration, wash with ethanol and deionized water three times respectively, and dry the sample at 60°C for 12 h to obtain a composite nano-photocatalyst.
[0064] Comparative Example 1
[0065] Weigh 4 mmol of bismuth nitrate pentahydrate into a beaker, add 80 mL of deionized water, and stir thoroughly at room temperature for 20 min; add 4 mmol of sodium chloride and stir thoroughly at room temperature for 30 min; transfer the obtained mixed solution to a 100 mL polytetrafluoroethylene reactor for solvothermal reaction at 160°C for 12 h; after the reaction, cool to room temperature and filter with suction, the filter membrane is a 0.22 μm organic microporous filter membrane; after filtration, wash with ethanol and deionized water three times respectively, and dry the sample at 60°C for 12 h to obtain a nanomaterial, which is recorded as BiOCl nanomaterial.
[0066] Photocatalytic activity test process: At room temperature, 0.40g of the BiOCl nanomaterial of this comparative example is placed in a 30cm*30cm*30cm closed reactor, which contains 10ppm of volatile organic matter toluene. The catalyst darkly adsorbs toluene gas in the reactor for 1h, and then turns on an 8W LED fluorescent line light (white light) to irradiate the catalyst material. The change in the concentration of toluene in the reactor can be detected by a gas chromatograph. The toluene content and degradation rate are calculated by the peak area of toluene in the chromatographic peak.
[0067] The photocatalytic activity of the prepared BiOCl nanomaterial was measured by degrading toluene under visible light. In this comparative example, the degradation rate of the BiOCl nanomaterial catalyst for catalytic degradation of toluene within 30 minutes was only 4.1%.
[0068] The products synthesized in Examples 1 to 4 and Comparative Example 1 were characterized by X-ray polycrystalline powder diffraction. According to the diffraction spectrum, Figure 1 As shown, the product synthesized in Comparative Example 1 is BiOCl; in Examples 1 to 4, new diffraction peaks appear at 27.3°, 37.8° and 39.5°. By comparing the standard card JCPDS 06-0249, it can be seen that these diffraction peaks correspond to the diffraction peaks of Bi single substance one by one, indicating that the method of the present invention can indeed produce a Bi / BiOCl composite material.
[0069] The samples synthesized in Example 3 and Comparative Example 1 were examined by scanning electron microscopy (SEM). It can be observed that the Bi / BiOCl-220 sample synthesized in Example 3 is mainly composed of microspheres formed by stacking nanosheets, and the diameter of the microspheres is about 1.0-3.0 μm. In addition, a small amount of nanospheres are deposited around the microspheres, and the size is about 200 nm, corresponding to the typical structure of Bi nanospheres. The sample synthesized in Comparative Example 1 is composed of nanosheets stacked in layers.
[0070] The samples synthesized in Example 3 and Comparative Example 1 were characterized and analyzed by UV-visible diffuse reflectance spectroscopy. The results showed that compared with the sample synthesized in Comparative Example 1, the sample synthesized in Example 3 had an absorption band in the visible light range, which also confirmed that the obtained catalyst had visible light activity, and the Bi element on Bi / BiOCl enhanced the visible light activity of the Bi / BiOCl catalyst through the SPR effect.
[0071] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. Application of Bi / BiOCl composite nano-photocatalyst in photocatalytic degradation of volatile organic compounds, characterized in that: The Bi / BiOCl composite nano-photocatalyst is placed in a volatile organic matter, and after a dark adsorption process, the volatile organic matter is degraded by visible light catalysis; the dark adsorption time is 1 to 3 hours; the volatile organic matter is toluene; the preparation method of the Bi / BiOCl composite nano-photocatalyst comprises the following steps: dissolving a bismuth salt in an organic solvent, then adding a chloride salt to form a mixed solution, and subjecting the mixed solution to a solvent thermal reaction to obtain a Bi / BiOCl composite nano-photocatalyst; the reaction temperature is 180 to 240°C; the organic solvent is ethylene glycol; the concentration of the bismuth salt in the mixed solution is 0.01 to 0.1 mol / L; the molar ratio of the bismuth salt to the chloride salt is 1:(1 to 2).
2. The use according to claim 1, characterized in that The reaction temperature is 220°C.
3. The use according to claim 1, characterized in that The reaction time is 6 to 24 hours.
4. The use according to claim 3, characterized in that The reaction time is 12 to 24 hours.
5. The use according to claim 1, characterized in that The bismuth salt includes at least one of bismuth nitrate pentahydrate and bismuth chloride; the chloride salt includes at least one of potassium chloride and sodium chloride.
6. The use according to claim 1, characterized in that The concentration of the bismuth salt in the mixed solution is 0.05 mol / L; the molar ratio of the bismuth salt to the chloride salt is 1:
1.
7. The use according to claim 1, characterized in that The step of forming the mixed solution further includes: stirring for 30-60 minutes.
Citation Information
Patent Citations
Preparation method of BiOCl photocatalyst with ultra-high degradation effect
CN110624576A
Bismuth / bismuth oxychloride microsphere photocatalyst as well as preparation method and application thereof
CN114433137A
